Measuring lucid dreaming skills: a new questionnaire (LUSK) - Schredl, Michael; Rieger, Janina; Göritz, Anja (International journal of dream research, 2018)
Lucid dreaming is the phenomenon of dreaming while knowing that one is dreaming but the skills within the lucid dream, e.g., carrying out successfully pre-arranged tasks, vary considerably from dreamer to dreamer – even in frequent lucid dreamers. In order to measure inter-individual differences in lucid dreaming skills, a ten-item questionnaire was developed. The internal consistency was high. Substantial correlations with the skills score, age, and lucid dream frequency were found whereas gender did not affect lucid dreaming skills in the present sample (N = 675). The next steps would be to validate the questionnaire, i.e., demonstrating that high lucid dreaming skills (LUSK) scores are predicting better performance in sleep laboratory experiments, e.g., performing pre-arranged eye movements or specifi c tasks.